Selective CO2 and H-2 adsorption in a chiral magnesium-based metal organic framework (Mg-MOF) with open metal sites - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Journal of Materials Chemistry, 2010)
A rare porous magnesium-based metal-organic framework, Mg-MOF-1 [Mg(3,5-PDC)(H2O)], was synthesized solvothermally in DMF. Structural determination by X-ray single-crystal diffraction technique reveals that this chiral MOF (space group P6(1)22) is constructed by helical assembly of Mg2+ ions with achiral 3,5-pyridine dicarboxylates and coordinating water molecules, to form a three-dimensional framework with parallel hexagonal channels. The structural detail of its 0D analogue Mg-MOF-2 [Mg(2,4-PDC)(H2O)(3)] has been discussed to show how subtle variation in the ligand architecture changes the resulting structure from 0D to 3D. Mg-MOF-1 remains robust and porous upon evacuation of the coordinating water molecules. This is the first report of a chiral hexagonal Mg-MOF synthesized from an achiral organic building unit. Open Mg metal sites show selective hydrogen (H-2) adsorption (ca. 0.8 wt% at 77 K) and carbon dioxide (CO2) uptake (ca. 0.7 mmol g(-1) at 298 K) over nitrogen at 1 atm. Ab initio quantum chemical calculation of adsorption energies and possible adsorption sites of hydrogen molecules are also reported.

Assembly of polyethyleneimine in the hexagonal mesophase of nonionic surfactant: effect of pH and temperature - Sharma, Kamendra P.; Choudhury, Chandan Kumar; Srivastava, Sonal; Davis, Hilda C.; Rajamohanan, P. R.; Roy, Sudip; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2011)
We investigate the dispersion of a pH responsive polymer, polyethyleneimine, PEI, in a hexagonal (H(1)) mesophase of a nonionic surfactant, C(12)E(9), and water, at pH ranging from basic (pH = 12.8) to acidic (pH = 1). While the C(12)E(9)/H(2)O phase behavior is independent of pH, we demonstrate that, in the PEI/C(12)E(9)/H(2)O system, changing the pH influences PEI-C(12)E(9) interactions, and thus, influences the isotropic-H(1) phase transition. With decrease in pH, there is increasing protonation of the PEI chain, and consequently, the chain extends. We show, using a combination of SAXs, optical microscopy and visual experiments, that the inclusion of PEI in a 1:1 surfactant water mixture, lowers the hexagonal-isotropic transition temperature, T. At higher pH = 12.8 T(HI) shows a pronounced decrease from SO to 13 degrees C on addition of PEI, and the PEI/C(12)E(9)/H(2)O system forms a transparent gel. At pH = 1, we observe qualitatively different behavior and an opaque gel forms below T(HI)= 25 degrees C. The isotropic-H(1) transition, in turn, influences the phase separation of PEI chains from the C(12)E(9)/H(2)O system. 2D NMR ROESY data provides evidence that there are strong surfactant PEI interactions at high pH that significantly reduce at lower pH. The NMR data is in accord with molecular dynamics simulations that show that surfactants strongly aggregate with unprotonated PEI chains, but not with fully protonated chains; thus, in this system, the pH controls a cascade of microstructural organization: increasing pH decreases chain protonation and increases polymer-surfactant interactions, resulting in suppression of the isotropic-H(1) transition to lower temperatures, thus, influencing the phase separation of PEI from the surfactant/water system.

Early stages of unwinding of zwitterionic alpha-helical homopolymeric peptides - Pandey, Prithvi Raj; Roy, Sudip (Chemical Physics Letters, 2011)
Unwinding mechanisms of helices of the zwitterionic polyalanine, polyleucine, and polylysine were studied using classical molecular dynamics simulation at 300 K temperature. Interestingly the helices of polyalanine and polyleucine start to unwind from the terminals, which is further relayed to the middle of the chain with time. Polylysine helix also starts to unwind from the terminals of the alpha-helical chain but the unwinding is not relayed to the middle. The reason behind this observation is investigated whether the presence of -NH(2) groups in the side chain of polylysine is influencing the unwinding. Two competitive mechanisms, fluctuation of the terminal residues and exchange of H-bonds between residues and water trigger the process of unwinding. (C) 2011 Elsevier B. V. All rights reserved.

Headgroup mediated water insertion into the DPPC billayer: a molecular dynamics study - Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2011)
Molecular dynamics simulation was performed on the 1,2-dipalmitoyl-sn-phosphocholine (DPPC) bilayer-water system using the GROMOS96 53a6 united atom force field. The transferability of force field was tested by reproducing the area per lipid within 3% accuracy from the experimental value. The simulation shows that water can penetrate much deeper inside the bilayer almost up to the starting point of the aliphatic chain. There is significant evidence from experiments that water goes deep in the DPPC bilayer, but it has not been reported from theoretical work. The mechanism of insertion of water deep inside the lipid bilayer is still not clear. In this report, for the first time the mechanism of water insertion deep into the bilayer has been proposed. Water transport occurs by the headgroup and its first solvation shell. The trimethyl ammonium (NMe3) group (headgroup of DPPC) has two stable conformations at the bilayer-water interface, one outside the bilayer and another inside it. The NMe3 group has a large clustering of water around it and takes the water molecules inside the bilayer with it during its entry into the bilayer. The water molecules penetrate into the bilayer with the help of the NMe3 group present at the headgroup of DPPC and eventually form hydrogen bonds with carbonyl oxygen present deep inside the bilayer. Structural characteristics at the bilayer-water interface region are also reported.

Structure and gas sorption behavior of a new three dimensional porous magnesium formate - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Inorganic Chemistry, 2011)
A new three-dimensional magnesium formate polymorph, namely, gamma-[Mg-3(O2CH)(6)] has been synthesized via in situ formate anion generation method. gamma-Mg-formate crystallizes in space group Pbcn, and structural determination by X-ray single crystal diffraction reveals a three-dimensional network of Mg2+ linked by formate anions. All formate anions possess similar binding mode to the metal center with one oxygen of a particular formate anion binds to one metal center (mu(1) oxygen) and other oxygen binds to two metal centers (mu(2) oxygen). N-2 adsorption studies indicate that the framework displays permanent porosity. The specific surface area of gamma-Mg-formate (BET, 120 m(2) gm(-1)) is lower than the alpha- polymorph (BET, 150 m(2) gm(-1)). However, the initial hydrogen uptake of gamma-Mg-formate reached almost 1.0 wt % when the adsorbate pressure approached 760 Torr at 77 K. This is higher than the hydrogen uptake of alpha-Mg-formate (0.6 wt %). gamma-Mg-formate, shows a moderate affinity and capacity for CO2 (3.4 angstrom kinetic diameter) at 298 K. The CO2 uptake at 760 Torr is 2.01 mmol gm(-1)(47.0 cc gm(-1)). Although this CO2 uptake is somewhat modest, it compares well with the CO2 uptake of several Mg-MOFs and ZIFs reported in the literature.

Distinctions in early stage unwinding mechanisms of zwitterionic, capped, and neutral forms of different alpha-helical homopolymeric peptides - Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2012)
Molecular dynamics simulations of alpha-helical polyalanine, polyleucine, polylysine, and poly(glutamic acid) with different forms of terminal groups in water at 300 K showed sharp distinctions in their unwinding mechanisms. Zwitterionic, capped, and neutral forms of polyalanine, polyleucine, and polylysine have been explored to elucidate their unwinding mechanism at very early stage, e.g., initial time window. Role of water in the unwinding mechanisms of the various helices has been envisaged. Also, it is evident from our calculations that the short- and long-range nonbonded interactions among the side chains is an important factor determining the unwinding mechanisms of the various homopolymeric alpha-helices. These findings can be helpful in constructing predictive models for understanding of the unwinding of alpha-helical proteins and peptides.

Molecular dynamics simulation of phosphoric acid doped monomer of polybenzimidazole: a potential component polymer electrolyte membrane of fuel cell - Pahari, Swagata; Choudhury, Chandan Kumar; Pandey, Prithvi Raj; More, Minal; Venkatnathan, Arun; Roy, Sudip (Journal of Physical Chemistry B, 2012)
Phosphoric acid doped polybenzimidazole is promising electrolyte membranes for high temperature (100 degrees C and above) fuel cells. Proton conduction is governed by the amount of phosphoric acid content in the polymer membrane. In this present work, we perform molecular dynamics simulations on phosphoric acid doped 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole (monomer unit of polybenzimidazole) to characterize the structural and dynamical properties at varying phosphoric acid content and temperature. From the structural analysis, we have predicted the arrangement of the phosphoric acids, formation of H-bonds in the system, and the contribution of different atoms toward H-bonding. We have also examined the stacking of 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole molecules and how their arrangement changes with the increasing amount of PA in the system with the help of cluster analysis. From the molecular dynamics simulation conducted at different temperatures and phosphoric acid doping level, we have predicted the diffusion of phosphoric acid and monomer. As a dynamic quantity, we have also calculated ring flipping of the imidazole ring of the monomer.

Structural, dynamical, and thermodynamical properties of carbon nanotube polycarbonate composites: a molecular dynamics study - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2012)
All-atom molecular dynamics simulations are performed on pure monomer and trimer of polycarbonate and their mixtures with different molecular weight percentages of embedded single walled carbon nanotubes at different temperatures to study the structural and dynamical properties of the composite system. The diffusion behaviors of monomer, trimer of polycarbonate and carbon nanotubes in composite matrices are investigated and compared with pure matrices in details. Both structural and dynamical properties indicate the weak interaction between the nanotubes and matrix molecules. The high tendency of nanotubes to form bundles is observed during simulation. The bundle formation free energy has been calculated from the potential of mean force calculations. The mechanism and energetics of bundle formation is explored in the atomistic scale. The formation of the carbon nanotube bundle is a favorable process in the oligomeric polycarbonate matrix.

Characterization of conformation and interaction of gene delivery vector polyethylenimine with phospholipid bilayer at different protonation state - Choudhury, Chandan Kumar; Kumar, Abhinaw; Roy, Sudip (Biomacromolecules, 2013)
Polyethylenimine (PEI) is a pH sensitive polymer possessing stretched and coiled conformation at low and high pH, respectively. It is an efficient gene delivery agent. Thus, the interaction of PEI with the biomembrane is very crucial to understand the gene delivery mechanism. In this report, we have investigated the structural properties of PEI and bilayer due to the interaction of PEI with lipid molecules. PEI has coil structure at high pH while at low pH it is elongated. The neutral PEI chain predominately settles itself at the bilayer water interface. We do not find any disruption or pore formation on the bilayer due to interaction of neutral PEI chain. PEI at low pH gets elongated due to electrostatic interaction between charges of the protonated sites. This protonated PEI chain interacts with bilayer membrane, which leads to formation of water/ion channel through the membrane. We have analyzed the structure of the channel and water dynamics along the channel.

Characterization of the structures and dynamics of phosphoric acid doped benzimidazole mixtures: a molecular dynamics study - More, Minal; Pahari, Swagata; Roy, Sudip; Venkatnathan, Arun (Journal of Molecular Modeling, 2013)
Benzimidazole-based polymer membranes like poly(2,5-benzimidazole) (ABPBI) doped with phosphoric acid (PA) are electrolytes that exhibit high proton conductivity in fuel cells at elevated temperatures. The benzimidazole (BI) moiety is an important constituent of these membranes, so the present work was performed in order to achieve a molecular understanding of the BI-PA interactions in the presence of varying levels of the PA dopant, using classical molecular dynamics (MD) simulations. The various hydrogen-bonding interactions, as characterized based on structural properties and hydrogen-bond lifetime calculations, show that both BI and PA molecules exhibit dual proton-acceptor/donor functionality. An examination of diffusion coefficients showed that the diffusion of BI decreases with increasing PA uptake, whereas the diffusion of PA slightly increases. The hydrogen-bond lifetime calculations pointed to the existence of competitive hydrogen bonding between various sites in BI and PA.
Keywords: Diffusion coefficient; Hydrogen bond; molecular dynamics; Radial distribution functions

Evidence and characterization of dynamic heterogeneity in binary mixtures of phosphoric acid and benzimidazole - Pahari, Swagata; Roy, Sudip (Journal of Chemical Physics, 2013)
We report here anomalous diffusions of components in mixtures of monomer of polybenzimidazole, i.e., 2-phenyl-1H, 1'H-5,5'-bibenzo[d] imidazole (BI) and phosphoric acid (PA) from molecular dynamics simulations. We have observed initial drop and further increase in self-diffusion constant for both monomer molecule (BI) and PA with gradual increase in PA concentration. The origin of such anomalous diffusion is identified in this work, which happens to be the presence of dynamic heterogeneity in each component of the binary mixture. We characterized microscopic picture of dynamical heterogeneity by finding correlation between dynamical heterogeneity and structural arrangement among the components of the binary system. Different types of H-bonding arrangements in the BI-PA systems at different concentration of PA are observed. The stability of the H-bonded network consisting of different types of H-bonds between BI and PA in the system has been studied by calculating the lifetime of various H-bonds. The results indicate that there are fast and slow moving PA molecules in the mixtures because of coexistence of different types of hydrogen bonds among the components of the mixture. (C) 2013 AIP Publishing LLC.

Heat transfer calculations for decomposition of structure i methane hydrates by molecular dynamics simulation - Baghel, Vikesh Singh; Kumar, Rajnish; Roy, Sudip (Journal of Physical Chemistry C, 2013)
Microcanonical ensemble molecular dynamics simulations of structure I methane hydrate is presented in this work to study the endothermic decomposition process. The mechanism of decomposition of methane hydrate as a function of time was explained at the molecular level. The initial temperature and pressure of the simulation were chosen so as to depict the natural gas hydrate in conditions of oceanic sediments. A more realistic strategy was developed to perform the microcanonical ensemble simulation of solid liquid interface of hydrate and amorphous water. Two water models, SPC/E and TIP4P, were used for the simulations, and the results of the simulations were compared. Heat transfer calculations were performed on the adiabatic system, and an attempt has been made to fit the MD simulation results to the heat balance equations derived from the heat transfer calculations. Estimates of the properties at the macroscopic scale, like the equilibrium temperature of methane hydrate and rate of supply of hot water for sustained release of methane from solid hydrate phase, were determined. The equilibrium temperature obtained by the above method was found to be in agreement with the experimentally observed value. Both the SPC/E and TIP4P water models gave similar results.

Is it possible to change wettability of hydrophilic surface by changing its roughness? - Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry Letters, 2013)
Wetting behavior of model rough surfaces made of hydrophilic square pillars is investigated. The hydrophilic pillars are equally spaced on hydrophilic surface. The surface roughnesses are altered by varying the pillar width and interpillar spacing. Wetting to dewetting transition is observed for these surfaces. This is one of the first accounts of observation from molecular simulations where hydrophilic surface converts into hydrophobic by changing its roughness. The extent of hydrophilicities are also changed to gain more insightful observations. Energies of the wetting to dewetting transitions are analyzed by calculating the contribution from water water and water surface energy components. A correlation between energy and the wetting to dewetting transition has been established, which rationally explains the observed water repellent nature of hydrophilic surface as a function of roughness.

Morphology and dynamics of carbon nanotube in polycarbonate carbon nanotube composite from dissipative particle dynamics simulation - Chakraborty, Souvik; Choudhury, Chandan Kumar; Roy, Sudip (Macromolecules, 2013)
Morphology and dynamics of carbon nanotube (CNT) in polycarbonate matrix with different mixing ratios are studied in mesoscale by using dissipative particle dynamics (DPD). We have used atomistic simulation to derive necessary interaction parameter for mesoscale DPD simulation for polycarbonate nanotube composite using Flory-Huggins theory. The diffusion and morphology of nanotubes in different concentrations (2%, 5%, 10%) are investigated. Diffusivity of nano tubes in polymer matrices is explored at different temporal regimes of simulation. Diffusion of nanotubes becomes significantly slow when bundling of nanotubes takes place. The bundle formation of nanotubes is observed in all of three mixtures with varying degrees of assembling and alignment Bundle size analysis is performed to study the extent of bundling affinity of CNTs in different filler concentrations. Size of the bundles of nanotubes is more in higher nanotube concentrations. In the 10% mixture percolation network is found to be formed by bundles of nanotubes.

Structural and dynamical properties of polyethylenimine in explicit water at different protonation states: a molecular dynamics study - Choudhury, Chandan Kumar; Roy, Sudip (Soft Matter, 2013)
PEI is a pH sensitive polymer which acts as a proton sponge in acidic conditions. Despite many experimental and theoretical efforts, a fundamental understanding of the structure and dynamics of linear PEI chains on the atomistic level at different protonation states in dilute solutions remains a topic of discussion. This report analyses the structural properties of PEI at different protonation states, which are representative of different pH, using all atomistic molecular dynamic simulations. The structural properties revealed that the polymer at high pH (basic medium) is highly coiled, while at low pH (strong acidic conditions) the chains are elongated. We studied the dynamics and ordering of water molecules that are part of the solvation shells of the PEI chains at different protonation states. We observe that the water molecules are ordered along the polymer backbone for a completely protonated PEI chain (i.e. in the case of acidic pH) and hop to the neighbouring solvation shell. The residence time and the self-diffusion of water molecules in the solvation shells and their activation barriers were also calculated and analysed further. We concluded the study by correlating the solvation shell water dynamics and the structure of the PEI chain at different protonation states.

Effect of gold nanoparticle on structure and fluidity of lipid membrane - Mhashal, Anil R.; Roy, Sudip (Plos One, 2014)
This paper deals with the effect of different size gold nanoparticles on the fluidity of lipid membrane at different regions of the bilayer. To investigate this, we have considered significantly large bilayer leaflets and incorporated only one nanoparticle each time, which was subjected to all atomistic molecular dynamics simulations. We have observed that, lipid molecules located near to the gold nanoparticle interact directly with it, which results in deformation of lipid structure and slower dynamics of lipid molecules. However, lipid molecules far away from the interaction site of the nanoparticle get perturbed, which gives rise to increase in local ordering of the lipid domains and decrease in fluidity. The bilayer thickness and area per head group in this region also get altered. Similar trend, but with different magnitude is also observed when different size nanoparticle interact with the bilayer.

Model atomistic protrusions favouring the ordering and retention of water - Pandey, Prithvi Raj; Roy, Sudip (Physical Chemistry Chemical Physics, 2014)
The ordering of water molecules near model linear atomistic protrusions is studied using classical molecular dynamics simulations. The protrusions are made up of Lennard-Jones particles of hydrophobic and hydrophilic blocks. Simulations are performed at a range of temperatures and pressures, keeping the position of the protrusions fixed. At different temperatures and pressures, the ordering and residence time of water molecules is enhanced on the surface of the hydrophilic block. Detailed analysis of the systems shows that the surface region is potentially the most energetically favorable for water molecules, which is consistent with the tetrahedral ordering of water molecules. A competition between energetics and structuring is observed from residence time calculations.

Vesicle structures from bolaamphiphilic biosurfactants: experimental and molecular dynamics simulation studies on the effect of unsaturation on sophorolipid self-assemblies - Dhasaiyan, Prabhu; Pandey, Prithvi Raj; Visaveliya, Nikunjkumar; Roy, Sudip; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2014)
The formation of giant-vesicle-like structures by self-assembling linolenic acid sophorolipid (LNSL) molecules is revealed. Sophorolipids belong to the class of bolaamphiphilic glycolipid biosurfactants. Interestingly, the number of double bonds present in the hydrophobic core of sophorolipids is seen to have a great influence on the type of self-assembled structures formed. Dye encapsulation results establish the presence of an aqueous compartment inside the LNSL vesicles. Molecular dynamics simulation (MD) studies suggest the existence of two possible conformations of LNSLs inside the self-assembled structures and that LNSL molecules arrange in layered structures.
Keywords: bolaamphiphiles; MD simulations; Self-assembly; sophorolipids; vesicles

Compact polar moieties induce lipid-water systems to form discontinuous reverse micellar phase - Kumar, Manoj; Patil, Naganath G.; Choudhury, Chandan Kumar; Roy, Sudip; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Soft Matter, 2015)
The role of molecular interactions in governing lipid mesophase organization is of fundamental interest and has technological implications. Herein, we describe an unusual pathway for monoolein/water reorganization from a bicontinuous mesophase to a discontinuous reverse micellar assembly, directed by the inclusion of polar macromolecules. This pathway is very different from those reported earlier, wherein the Fd3m phase formed only upon addition of apolar oils. Experiments and molecular dynamics simulations indicate that hydrophilic ternary additives capable of inducing discontinuous phase formation must (i) interact strongly with the monoolein head group and (ii) have a compact molecular architecture. We present a detailed investigation that contrasts a monoolein-water system containing polyamidoamine (PAMAM) dendrons with one containing their linear analogs. The Fd3m phase forms only on the addition of PAMAM dendrons but not their linear analogs. Thus, the dendritic architecture of PAMAM plays an important role in determining lipid mesophase behavior. Both dendrons and their linear analogs interact strongly with monoolein through their amine groups. However, while linear polymers adsorb and spread on monoolein, dendrons form aggregates that interact with the lipid. Dendrons induce formation of an intermediate reverse hexagonal phase, which subsequently restructures into the Fd3m phase. Finally, we demonstrate that other additives with compact structures that are known to interact with monoolein, such as branched polyethylenimine and polyhedral silsesquioxane cages, also induce the formation of the Fd3m phase.

Methane hydrate formation in a test sediment of sand and clay at various levels of water saturation - Kumar, Asheesh; Sakpal, Tushar; Roy, Sudip; Kumar, Rajnish (Canadian Journal of Chemistry, 2015)
Kinetics of methane hydrate formation with different ratios of silica sand and clay and different water saturations were studied. At suitable temperature and methane gas pressure, water in the void spaces of silica sand packing and intercalated area of clay were converted into hydrate. It was observed that the rate of hydrate formation increases with higher void space in the packing, and addition of clay in test sediment decreases water to hydrate conversion as well as rate of hydrate formation. Maximum water to hydrate conversion of 60.0% was achieved in pure silica sand bed at 75% water saturation. Presence of fine clay particles is expected to reduce the void spaces and thus may hinder effective mass transfer of hydrate forming gases in the bed. However, it is also possible that the bentonite clay used in this work may actually inhibit hydrate growth. Additional experiments in stirred tank reactor were carried out to understand the inhibiting effect of bentonite clay for hydrate formation.
Keywords: clay; formation kinetics; methane hydrate; Silica sand; water saturation

Molecular dynamics study of model SI clathrate hydrates: the effect of guest size and guest-water interaction on decomposition kinetics - Das, Subhadip; Baghel, Vikesh Singh; Roy, Sudip; Kumar, Rajnish (Physical Chemistry Chemical Physics, 2015)
One of the options suggested for methane recovery from natural gas hydrates is molecular replacement of methane by suitable guests like CO2 and N-2. This approach has been found to be feasible through many experimental and molecular dynamics simulation studies. However, the long term stability of the resultant hydrate needs to be evaluated; the decomposition rate of these hydrates is expected to depend on the interaction between these guest and water molecules. In this work, molecular dynamics simulation has been performed to illustrate the effect of guest molecules with different sizes and interaction strengths with water on structure I (SI) hydrate decomposition and hence the stability. The van der Waals interaction between water of hydrate cages and guest molecules is defined by Lennard Jones potential parameters. A wide range of parameter spaces has been scanned by changing the guest molecules in the SI hydrate, which acts as a model gas for occupying the small and large cages of the SI hydrate. All atomistic simulation results show that the stability of the hydrate is sensitive to the size and interaction of the guest molecules with hydrate water. The increase in the interaction of guest molecules with water stabilizes the hydrate, which in turn shows a slower rate of hydrate decomposition. Similarly guest molecules with a reasonably small (similar to Helium) or large size increase the decomposition rate. The results were also analyzed by calculating the structural order parameter to understand the dynamics of crystal structure and correlated with the release rate of guest molecules from the solid hydrate phase. The results have been explained based on the calculation of potential energies felt by guest molecules in amorphous water, hydrate bulk and hydrate-water interface regions.

Propensity of self-assembled leucine-lysine diblock copolymeric alpha-helical peptides to remain in parallel and antiparallel alignments in water - Sarkar, Sujit; Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Molecular dynamics Simulation study of alpha-helical diblock copolypeptides: preassembled in parallel and antiparallel alignments in water are presented. The assembled peptide lamellar structures were not disrupted even: after performing three step simulation protocols. Primarily hydrogen bonds between peptide are responsible for the stability: The analysis of the trajectory also suggests that Water plays a significant role in favoring self assembly We have detected continuous hydrogen bonded network structure, which is further responsible for the stability Of the lamellar structures. We have performed a detailed analysis of the hydrogen bonded network structure and its length. Further, free energy calculations revealed that the degree of stability for both lamellae are similar. The present study provides structural insight into the stability of self-assembled structures of block copolypeptides.

Proton transport mechanism of imidazole, triazole and phosphoric acid mixtures from ab initio molecular dynamics simulations - Pahari, Swagata; Roy, Sudip (Physical Chemistry Chemical Physics, 2015)
We performed first principles molecular dynamics simulations to elucidate the mechanism and role of 1,2,3-triazole in proton transport while it is mixed with phosphoric acid (PA) and a phosphoric acid imidazole mixture. PA doped imidazole based polymer acts as an efficient polyelectrolyte membrane for fuel cells. The conductivity of this membrane increases when triazole is added to the system. For the first time we performed ab initio molecular dynamics simulations of complex mixtures of PA, imidazole and triazole. We have quantitatively estimated the structural diffusion and vehicular motion of protons. We found that upon the addition of triazole in PA and the PA imidazole mixture, the structural diffusion of protons increases significantly. The mechanism of proton transport is different when triazole is added to the mixture. We have also identified two different paths for structural diffusion (constructive and non-constructive) that contribute to long and short range proton transport.

Self-assembly of phospholipids on flat supports - Mhashal, Anil R.; Roy, Sudip (Physical Chemistry Chemical Physics, 2015)
The current study deals with the self-assembly of phospholipids on flat supports using the Martini coarse grain model. We reported here the effect of the hydrophilic and hydrophobic nature of the solid supports on the lipid self-assembly. The hydrophilic and hydrophobic supports were modeled on the basis of water droplet simulations. The present work addresses the self-assembly mechanism of lipids on eight different supports with different strengths of hydrophilicity and hydrophobicity. We demonstrated how interplay between the interactions of lipid and water with the support can guide the lipid self-assembly process. Thereafter, we calculated the energetics of the components of the system to quantify the competitions between water and a lipid head-group with hydrophilic supports. Finally, the properties of the self-assembled bilayers were also analyzed and reported here.

Structure of nanorod assembly in the gyroid phase of diblock copolymer - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Diblock copolymers undergo microphase separation to form various microstructures, for example, lamellar, gyroid, cylindrical, cubic phases depending on compostion and segregation strength (Flory-Huggins parameter chi). Thus, it can act as template to organize doped nanomaterials into different 3D self-assembled structures located within the block copolymer matrix. Gyroid phase is One of the microstructures formed by block copolymer. It has a curved interfacial surface providing confinements throughout the matrix and thus can regulate the shape and sizes of self-assembled nanorods doped in it. Mesoscale simulation of model systems has been performed to explore the structure and dynamics of self-assembly of bundles formed by nanorods of different flexibilities in the gyroid phase of diblock copolymer matrix. Bundles of different shapes and sizes have been found to be formed depending on the nanorod bending flexibility and copolymer-nanorod interactions. The shape anisotropy (kappa(2)) and radius of gyration (R-g(2)) of bundles situated at different interfacial confining locations of block copolymer-matrices have been investigated as a function of nanorod flexibility and nanorod-diblock copolymer miscibility.

Effect of polyvinylpyrrolidone at methane hydrate-liquid water interface. application in flow assurance and natural gas hydrate exploitation - Choudhary, Nilesh; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Fuel, 2016)

Free energy of bare and capped gold nanoparticles permeating through a lipid bilayer - Mhashal, Anil R.; Roy, Sudip (Chemphyschem, 2016)
Herein, we study the permeation free energy of bare and octane-thiol-capped gold nanoparticles (AuNPs) translocating through a lipid membrane. To investigate this, we have pulled the bare and capped AuNPs from bulk water to the membrane interior and estimated the free energy cost. The adsorption of the bare AuNP on the bilayer surface is energetically favorable but further loading inside it requires energy. However, the estimated free-energy barrier for loading the capped AuNP into the lipid membrane is much higher compared to bare AuNP. We also demonstrate the details of the permeation process of bare and capped AuNPs. Bare AuNP induces the curvature in the lipid membrane whereas capped AuNP creates an opening in the interacting monolayer and get inserted into the membrane. The insertion of capped AuNP induces a partial unzipping of the lipid bilayer, which results in the ordering of the local lipids interacting with the nanoparticle. However, bare AuNP disrupts the lipid membrane by pushing the lipid molecules inside the membrane. We also analyze pore formation due to the insertion of capped AuNP into the membrane, which results in water molecules penetrating the hydrophobic region.

Probing the ATP-induced conformational flexibility of the PcrA helicase protein using molecular dynamics simulation - Mhashal, Anil R.; Choudhury, Chandan Kumar; Roy, Sudip (Journal of Molecular Modeling, 2016)
Helicases are enzymes that unwind double-stranded DNA (dsDNA) into its single-stranded components. It is important to understand the binding and unbinding of ATP from the active sites of helicases, as this knowledge can be used to elucidate the functionality of helicases during the unwinding of dsDNA. In this work, we investigated the unbinding of ATP and its effect on the active-site residues of the helicase PcrA using molecular dynamic simulations. To mimic the unbinding process of ATP from the active site of the helicase, we simulated the application of an external force that pulls ATP from the active site and computed the free-energy change during this process. We estimated an energy cost of similar to 85 kJ/mol for the transformation of the helicase from the ATP-bound state (1QHH) to the ATP-free state (1PJR). Unbinding led to conformational changes in the residues of the protein at the active site. Some of the residues at the ATP-binding site were significantly reoriented when the ATP was pulled. We observed a clear competition between reorientation of the residues and energy stabilization by hydrogen bonds between the ATP and active-site residues. We also checked the flexibility of the PcrA protein using a principal component analysis of domain motion. We found that the ATP-free state of the helicase is more flexible than the ATP-bound state.
Keywords: ATP; DNA helicase; PcrA; Residue reorientation; Translocation; Umbrella sampling; Unwinding

Scalability of coarse-grained potentials generated from iterative boltzmann inversion forpolymers: case study on polycarbonates - Choudhury, Chandan Kumar; Carbone, Paola; Roy, Sudip (Macromolecular Theory and Simulations, 2016)
Using systematic coarse-grained (CG) techniques such as iterative Boltzmann inversion (IBI) is an efficient means to simulate high molecular weight polymer melts within reasonable computational time. One drawback of such an approach is however the need to carry out extensive atomistic simulations in order to extrapolate the necessary distributions to derive the inter and intrabead force field parameters. Here it is shown that it is possible to use atomistic simulations of relative short oligomers to develop the CG model for high molecular weight polymers. In particular for the specific case of polycarbonates, it is found that the structural properties (end-to-end distance, radius of gyration and their distributions) are similar irrespective of whether the CG potentials are derived from 5-mer or 10-mer melt systems. Dynamical properties of the CG systems are smoother and faster than the atomistic ones. Scaling factor, derived by overlapping the CG mean square displacement curves (obtained from different CG IBI potentials) over the atomistic ones, also scales the autocorrelation functions. A prediction of the dynamical scaling factor in the case of the unavailability of atomistic simulations is also discussed. The dynamical properties of the CG melts are modeled reasonably well by all the CG potentials derived from atomistic simulations of short oligomers.

Structural and conformational properties of polybenzimidazoles in melt and phosphoric acid solution: a polyelectrolyte membrane for fuel cells - Pahari, Swagata; Roy, Sudip (RSC Advances, 2016)
Poly[2,2'-(p-phenylene)-5,5'-bibenzimidazole (PBI) and poly(2,5-benzimidazole) (ABPBI) doped with phosphoric acid (PA) are considered as potential polymer electrolyte membranes for high temperature fuel cells. Conformational and structural properties of polymer chains in the presence of PA govern the function of the membrane. Therefore, in this work, a single chain conformational analysis of ABPBI and PBI in melt as well as in PA was performed using classical molecular dynamics simulations. End-to-end distance and the radius of gyration reveal significant changes in the conformations of PBI and ABPBI in PA. The structural changes are analyzed locally segment-wise as well as globally in these polymers. The shape and nature of the curvature along the chain is found to be significantly different for ABPBI and PBI. The role of the solvent (PA) on the chain backbone structure is explored for PA doped ABPBI and PBI chains. The PA arrangement along the backbone confirms that benzimidazole density in the case of both of the polymers determines the PA absorbing capacity. The H-bonding interactions between various atoms of the polymer backbone and the atoms of the PA molecules are evaluated along the polymer chain which relates to the arrangement of PA along the backbone. The reasons for the varying number of H-bonds along ABPBI and PBI which in turn has a significant effect on the stiffness of the chains are investigated.

Structural insight into self assembly of sophorolipids: a molecular dynamics simulation study - Pandey, Prithvi Raj; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Roy, Sudip (Zeitschrift Fur Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2016)
Sophorolipids contain hydrophilic head groups at the ends of a long hydrophobic tail. As a result, sophorolipids can self assemble into variety of structures in water. Atomistic self assembly simulations of sophorolipids are performed in water. Two sophorolipids, oleic acid sophorolipid and linolenic acid sophorolipid, differing in number of double bonds in the hydrophobic tail are considered for this study. Long time self assembly simulations are performed considering 1 :3 lipid to water ratio by weight for both oleic and linolenic acid sophorolipids. In addition to 1 : 3 ratio, long time self assembly simulations are also performed with 1 : 1 and 1 : 2 ratios for linolenic acid sophorolipids. Distinctions in structural arrangements of sophorolipid molecules in the self assembled configuration for all the systems are investigated. The present study aims to provide structural insight into the different self assembled configurations of sophorolipids in water.
Keywords: MD Simulation; self assembly; sophorolipids; United Atom Force Field

Transferability of different classical force fields for right and left handed alpha-helices constructed from enantiomeric amino acids - Biswas, Santu; Sarkar, Sujit; Pandey, Prithvi Raj; Roy, Sudip (Physical Chemistry Chemical Physics, 2016)
Amino acids can form D and L enantiomers, of which the L enantiomer is abundant in nature. The naturally occurring L enantiomer has a greater preference for a right handed helical conformation, and the D enantiomer for a left handed helical conformation. The other conformations, that is, left handed helical conformations of the L enantiomers and right handed helical conformations of the D enantiomers, are not common. The energetic differences between left and right handed alpha helical peptide chains constructed from enantiomeric amino acids are investigated using quantum chemical calculations (using the M06/6-311g(d,p) level of theory). Further, the performances of commonly used biomolecular force fields (OPLS/AA, CHARMM27/CMAP and AMBER) to represent the different helical conformations (left and right handed) constructed from enantiomeric (D and L) amino acids are evaluated. 5- and 10-mer chains from D and L enantiomers of alanine, leucine, lysine, and glutamic acid, in right and left handed helical conformations, are considered in the study. Thus, in total, 32 a-helical polypeptides (4 amino acids x 4 conformations of 5-mer and 10-mer) are studied. Conclusions, with regards to the performance of the force fields, are derived keeping the quantum optimized geometry as the benchmark, and on the basis of phi and psi angle calculations, hydrogen bond analysis, and different long range helical order parameters.

Validation of force fields of rubber through glass-transition temperature calculation by microsecond atomic-scale molecular dynamics simulation - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Journal of Physical Chemistry B, 2016)
Microsecond atomic-scale molecular dynamics simulation has been employed to calculate the glass-transition temperature (T-g) of cis- and trans-1,4-polybutadiene (PB) and 1,4-polyisoprene (PI). Both all-atomistic and united-atom models have been simulated using force fields, already available in literature. The accuracy of these decade old force fields has been tested by comparing calculated glass-transition temperatures to the corresponding experimental values. T-g depicts the phase transition in elastomers and substantially affects various physical properties of polymers, and hence the reproducibility of T-g becomes very crucial from a thermodynamic point of view. Such validation using T-g also evaluates the ability of these force fields to be used for advanced materials like rubber nanocomposites, where T-g is greatly affected by the presence of fillers. We have calculated T-g for a total of eight systems, featuring all-atom and united-atom models of cis- and trans-PI and-PB, which are the major constituents of natural and synthetic rubber. Tuning and refinement of the force fields has also been done using quantum-chemical calculations to obtain desirable density and T-g. Thus, a set of properly validated force fields, capable of reproducing various macroscopic properties of rubber, has been provided. A novel polymer equilibration protocol, involving potential energy convergence as the equilibration criterion, has been proposed. We demonstrate that not only macroscopic polymer properties like density, thermal expansion coefficient, and T-g but also local structural characteristics like end-to-end distance (R) and radius of gyration (R-g) and mechanical properties like bulk modulus have also been equilibrated using our strategy. Complete decay of end-to-end vector autocorrelation function with time also supports proper equilibration using our strategy.

Drug-triggered self-assembly of linear polymer into nanoparticles for simultaneous delivery of hydrophobic and hydrophilic drugs in breast cancer cells - Palvai, Sandeep; Anandi, Libi; Sarkar, Sujit; Augustus, Meera; Roy, Sudip; Lahiri, Mayurika; Basu, Sudipta (ACS Omega, 2017)
Breast cancer is the most devastating disease among females globally. Conventional chemotherapeutic regimen relies on the use of highly cytotoxic drugs as monotherapy and combination therapy leading to severe side effects to the patients as collateral damage. Moreover, combining hydrophobic and hydrophilic drugs create erratic biodistribution and suboptimal medicinal outcome. Hence, packaging multiple drugs of diverse mechanisms of action and biodistribution for safe delivery into tumor tissues with optimal dosages is indispensable for next-generation breast cancer therapy. To address these, in this report, we describe a unique cisplatin-triggered self-assembly of linear polymer into 3D-spherical sub 200 nm particles. These nano-particles comprise a hydrophobic (paclitaxel) and hydrophilic drug (cisplatin) simultaneously in a single particle. Molecular dynamics simulation revealed hydrophilic-hydrophilic interaction and interchain H-bonding as underlying mechanisms of self-assembly. Confocal microscopy studies evidently demonstrated that these novel nanoparticles can home into lysosomes in breast cancer cells, fragment subcellular nuclei, and prevent cell division, leading to improved breast cancer cell death compared to free drug combination. Moreover, 3D-breast tumor spheroids were reduced remarkably by the treatment of these nanoparticles within 24 h. These dual-drug-loaded self-assembled polymeric nanoparticles have prospective to be translated into a clinical strategy for breast cancer patients.

Effect of shape of protrusions and roughness on the hydrophilicity of a surface - Chowdhury, Sheelan Sengupta; Pandey, Prithvi Raj; Kumar, Rajnish; Roy, Sudip (Chemical Physics Letters, 2017)
We have investigated wetting of model rough surfaces made up of hydrophilic triangular and hexagonal pillars (protrusions). The surface roughnesses are altered by varying the area of the rough surface, the height of the pillars, and the surface interactions to the water. We have established a correlation between structure i.e., the shape of a pillar, which actually depends on the number of edges (due to shape), and the wetting phenomena. We have found that surface with higher number of edges repels water at lower roughness value. We explain the correlation by analyzing the variation of interactions energy components and density profiles of water on the structured surfaces. (C) 2017 Elsevier B.V. All rights reserved.

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.

Effect of sodium dodecyl sulfate surfactant on methane hydrate formation: a molecular dynamics study - Choudhary, Nilesh; Hande, Vrushali R.; Roy, Sudip; Chakrabarty, Suman; Kumar, Rajnish (Journal of Physical Chemistry B, 2018)
In experimental studies, it has been observed that the presence of sodium dodecyl sulfate (SDS) significantly increases the kinetics of hydrate formation and the final water-to-hydrate conversion ratio. In this study, we intend to understand the molecular mechanism behind the effect of SDS on the formation of methane hydrate through molecular dynamics simulation. Hydrate formation conditions similar to that of laboratory experiments were chosen to study hydrate growth kinetics in 1 wt % SDS solution. We also investigate the effect of interactions with isolated SDS molecules on methane hydrate growth. It was observed that the hydrophobic tail part of the SDS molecule favorably interacts with the growing hydrate surface and may occupy the partial hydrate cages while the head groups remain exposed to water.

Mechanism of the formation of microphase separated water clusters in a water-mediated physical network of perfluoropolyether tetraol - Deshpande, Ashwini A.; Torris, Arun A. T.; Pahari, Swagata; Menon, Shamal K.; Badiger, Manohar V.; Rajamohanan, P. R.; Wadgaonkar, Prakash P.; Roy, Sudip; Tonelli, Claudio (Soft Matter, 2018)
Perfluoropolyether tetraol (PFPE tetraol) possesses a hydrophobic perfluoropolyether chain in the backbone and two hydroxyl groups at each chain terminal, which facilitates the formation of hydrogen bonds with water molecules resulting in the formation an extended physical network. About 3 wt% water was required for the formation of the microphase separated physical network of PFPE tetraol. The mechanism responsible for the microphase separation of water clusters in the physical network was studied using a combination of techniques such as NMR spectroscopy, molecular dynamics (MD) simulations and DSC. MD simulation studies provided evidence for the formation of clusters in the PFPE tetraol physical network and the size of these clusters increased gradually with an increase in the extent of hydration. Both MD simulations and NMR spectroscopy studies revealed that these clusters position themselves away from the hydrophobic backbone or vice versa. The presence of intra-and inter-chain aggregation possibility among hydrophilic groups was evident. DSC results demonstrated the presence of tightly and loosely bound water molecules to the terminal hydroxyl groups of PFPE tetraol through hydrogen bonding. The data from all the three techniques established the formation of a physical network driven by hydrogen bonding between the hydrophilic end groups of PFPE tetraol and water molecules. The flexible nature of the PFPE tetraol backbone and its low solubility parameter favour clustering of water molecules at the terminal groups and result in the formation of a gel.

Molecular view of CO2 capture by polyethylenimine: role of structural and dynamical heterogeneity - Sharma, Pragati; Chakrabarty, Suman; Roy, Sudip; Kumar, Rajnish (Langmuir, 2018)
The molecular thermodynamics and kinetics of CO2 sorption in Polyethylenimine (PEI) melt have been investigated systematically using GCMC and MD simulations. We elucidate presence of significant structural and dynamic heterogeneity associated with the overall absorption process. CO2 adsorption in a PEI membrane shows a distinct two-stage process of a rapid CO2 adsorption at the interfaces (hundreds of picoseconds) followed by a significantly slower diffusion limited release toward the interior bulk regions of PEI melt (hundreds of nanoseconds to microseconds). The spatial heterogeneity of local structural features of the PEI chains lead to significantly heterogeneous absorption characterized by clustering and trapping of CO2 molecules that then lead to subdiffusive motion of CO2. In the complex interplay of interaction and entropy, the latter emerges out to be the major determining factor with significantly higher solubility of CO2 near the interfaces despite having lower density of binding amine groups. Regions having higher free-volume (entropically favorable) viz. interfaces, pores and loops demonstrate higher CO2 capture ability. Various local structural features of PEI conformations, for example, inter- and intrachain loops, pores of different radii, and di- or tricoordinated pores are explored for their effects on the varying CO2 adsorption abilities.

Phase diagram of self-assembled sophorolipid morphologies from mesoscale simulations - Sarkar, Sujit; Chakraborty, Souvik; Roy, Sudip (Journal of Molecular Liquids, 2018)
We have constructed a phase diagram from the self-assembled morphologies of linolenic acid sophorolipid in water by performing mesoscale simulations in different concentrations. The dependence of morphologies and its properties of the self-assembled structure as a function of the concentration of bolaamphiphile in water are investigated. Two hydrophilic head groups and one hydrophobic tail group of bolaamphiphile have been mapped to beads for mesoscale simulation. The interaction parameters between different beads are calculated using Flory-Huggins solution theory. Flory-Huggins x-parameters have been calculated from atomistic simulation and experimental data of pure components constituting linolenic acid sophorolipid. We have obtained different self-assembled morphologies depending upon the concentrations of sophorolipid in water. We have explored the arrangements of hydrophobic and hydrophilic groups of the sophorolipid chains in the different morphologies. The sophorolipid chains found to be present in different structural arrangements. The residence time and flip frequency of these lipids in different orientations have been calculated and discussed in this work. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Bolaamphiphile; Flip frequency; Mesoscale simulation; Orientation of chains; Self-assembly

Comparison of different water models for melting point calculation of methane hydrate using molecular dynamics simulations - Choudhary, Nilesh; Chakrabarty, Suman; Roy, Sudip; Kumar, Rajnish (Chemical Physics, 2019)
Molecular dynamics simulation is a powerful tool to understand the gas hydrate nucleation, growth, and dissociation at molecular level. Prerequisite of super-cooling during gas hydrate formation and a certain degree of super-healing during melting shows significant hysteresis in the transition between solid and liquid state due to large nucleation barrier. Different water models quantitatively differ in their prediction of thermodynamic and kinetic properties of bulk water, including phase behaviour. The present work carries out a systematic investigation of the effect of the chosen water model on the phase behaviour, in particular, the decomposition of methane hydrate. Void-induced melting has been used to predict the melting point of methane hydrate using TIP4P/Ice, TIP4P/2005, TIP4P, and SPC/E water models. This method avoids the need for a predetermined interface for melting point calculations and thus may have its importance in identifying dissociation kinetics of bulk hydrate.
Keywords: decomposition; Gas hydrates; Void-induced melting; Water models

Impact of plasticizer addition on molecular properties of polybutadiene rubber and its manifestations to glass transition temperature - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Macromolecular Theory and Simulations, 2019)
Effect of blending low and high T-g polymer on the structural, spatial, and temporal properties of the polybutadiene rubber are investigated using molecular dynamics simulations. It is elucidated that smaller chain length counterpart of polybutadiene (5mer-OB) acts as plasticizer for the polybutadiene rubber matrix (32mer-PB). Observed flexibility at macroscopic level by plasticizer addition is corroborated at the molecular level in the form of lower conformational rigidity and faster diffusion of polybutadiene chains in the mixtures. It is inferred that plasticizers decreases T-g of the matrix, due to cooperative influence of decreased chain packing and rigidity. Opposite effect is observed in mixtures with high T-g polymer, polystyrene. T-g of the mixtures showed substantial dependence on the type, concentration, chain length as well as miscibility of plasticizers in the matrix. However, the effect of increasing chain length is more pronounced but counter-controlled by the spatially heterogeneous distribution of the plasticizer. Clustering of polystyrene chains induced significant dynamic heterogeneity in the homogeneous polybutadiene matrix, which apparently lead to reduced plasticization effect. Addition of plasticizers in rubber induce discernible changes in the structural and dynamic properties of the rubber matrix, which manifest as the variation in glass transition and explains the real-life activity of plasticizers.
Keywords: Glass transition temperature; MD Simulation; plasticizer action; polybutadiene rubber; Polystyrene; spatial and dynamic heterogeneity

Methane recovery from marine gas hydrates: a bench scale study in presence of low dosage benign additives - Bhattacharjee, Gaurav; Choudhary, Nilesh; Barmecha, Vivek; Kushwaha, Omkar S.; Pande, Nawal K.; Chugh, Parivesh; Roy, Sudip; Kumar, Rajnish (Applied Energy, 2019)
De-pressurization is one approach which has been found to be economically feasible for methane recovery from marine hydrates. Hydrate dissociation being an endothermic process suggests that de-pressurization alone would not be sufficient and some additional stimulation would be required for sustained production from one such reservoir. Thermal stimulation may overcome the challenge posed by the endothermic dissociation process; however, economically it may not be ideal. A possible way out is to use thermal stimulation, but at relatively low temperatures as compared to conventional practice. This would be economical and can be accomplished in the presence of small doses of additives mixed in with the water stream used for thermal stimulation. In the present study, a number of benign additives were identified which when used in low concentrations enhance the kinetics of methane hydrate dissociation compared to pure water. Additives were first shortlisted from a wide potential pool using quantum mechanical calculations. These additives were later tested for their efficacy in stirred tank reactor to quickly identify the best additives for the job and few selected additives were then studied in a larger bench scale setup (fixed bed configuration) where they were injected in the form of an additive-water stream to dissociate already formed hydrates. Factors such as toxicity of the additive, fluidity of additive-water stream, foam formation on mixing of additive with water, etc. were also taken into account. An energy and efficiency analysis revealed that reported additives enhance the energy ratio and thermal efficiency of the process as compared to pure water stimulation.
Keywords: Bench scale; kinetics; Marine hydrate; methane hydrate; Methane recovery; Natural gas hydrate; Process

Molecular dynamics study on growth of carbon dioxide and methane hydrate from a seed crystal - Nakate, Prajakta; Ghosh, Bappa; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Chinese Journal of Chemical Engineering, 2019)
In the current work, molecular dynamics simulation is employed to understand the intrinsic growth of carbon dioxide and methane hydrate starting from a seed crystal of methane and carbon dioxide respectively. This comparison was carried out because it has relevance to the recovery of methane gas from natural gas hydrate reservoirs by simultaneously sequestering a greenhouse gas like CO2. The seed crystal of carbon dioxide and methane hydrate was allowed to grow from a super-saturated mixture of carbon dioxide or methane molecules in water respectively. Two different concentrations (1:6 and 1:8.5) of CO2/CH4 molecules per water molecule were chosen based on gas-water composition in hydrate phase. The molecular level growth as a function of time was investigated by all atomistic molecular dynamics simulation under suitable temperature and pressure range which was well above the hydrate stability zone to ensure significantly faster growth kinetics. The concentration of CO2 molecules in water played a significant role in growth kinetics, and it was observed that maximizing the CO2 concentration in the aqueous phase may not result in faster growth of CO2 hydrate. On the contrary, methane hydrate growth was independent of methane molecule concentration in the aqueous phase. We have validated our results by performing experimental work on carbon dioxide hydrate where it was seen that under conditions appropriate for liquid CO2, the growth for carbon dioxide hydrate was very slow in the beginning. (C) 2019 The Chemical Industry and Engineering Society of China, and Chemical Industry Press Co., Ltd. All rights reserved.
Keywords: Cage dynamics; CH4 recovery; CO2 sequestration; F-4 order parameter; kinetics; Natural gas hydrate; Thermodynamics

Glass transition temperature of polybutadiene and polyisoprene from high temperature segmental relaxation correlation using molecular dynamics - Sharma, Pragati; Roy, Sudip (Soft Materials, 2020)
Predicting glass transition temperature for rubber and rubber composites is immensely important for tire industry for the development of products and fine-tune process conditions. Molecular dynamics simulation is been used to predict glass transition temperature as a function of molecular-level structural changes, e.g., composition (functional groups), topology, and polymerization. However, prediction of glass transition temperature within experimental error bar from molecular dynamics simulation is only possible from all atomistic description (model) of the system as united atom and coarse-grained models under-predict the values. Conventional way of calculation of glass transition temperature from density (or any other properties which show sharp transition)-temperature plots are computationally very demanding because of atomistic simulations and simulations below the glass transition point, i.e., in glassy state. Here we report a novel method for calculation of glass transition temperature using only segmental relaxation correlation functions calculated at higher temperatures, i.e., above glass transition temperature. We have presented a protocol here and shown for two polymeric systems polybutadiene and polyisoprene. We believe this method cuts the computational cost of predicting glass transition temperature by one-third and will be applicable for industrial applications for structure-property validations.
Keywords: Glass transition temperature; molecular dynamics simulation; Polymers; rubber